2015
DOI: 10.1016/j.neulet.2015.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of soluble platelet-derived growth factor receptor-β from human brain pericytes

Abstract: Platelet-derived growth factor receptor-β (PDGFRβ) is expressed in the brain by vascular mural cells - brain capillary pericytes and arterial vascular smooth muscle cells (VSMCs). Recent evidence shows that blood-brain barrier (BBB) disruption and increased permeability, especially in the hippocampus, positively correlates with elevated levels of soluble PDGFRβ (sPDGFRβ) in cerebrospinal fluid (CSF) in patients with mild dementia. To determine which vascular cell type(s) contributes to increased sPDGFRβ in CSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(121 citation statements)
references
References 34 publications
3
113
0
Order By: Relevance
“…In this technique, leakage of gadolinium contrast agent into the brain enables the regional CNS BBB permeability constant, K trans , to be quantified using the Patlak analysis method 49,65,66 . A study that compared BBB breakdown in the hippocampus in individuals with MCI compared to age-matched controls found that the extent of BBB breakdown was not affected by vascular risk factors 49 , but correlated with increased CSF levels of soluble platelet-derived growth factor receptor-β (PDGFRβ), a marker of pericyte injury 49,67 . BBB breakdown in the hippocampus occurred prior to hippocampal atrophy 49 , which is typically seen early in AD 68,69 , raising the possibility that BBB breakdown might precede neurodegeneration.…”
Section: Neuroimaging Evidence Of Bbb Disruptionmentioning
confidence: 99%
“…In this technique, leakage of gadolinium contrast agent into the brain enables the regional CNS BBB permeability constant, K trans , to be quantified using the Patlak analysis method 49,65,66 . A study that compared BBB breakdown in the hippocampus in individuals with MCI compared to age-matched controls found that the extent of BBB breakdown was not affected by vascular risk factors 49 , but correlated with increased CSF levels of soluble platelet-derived growth factor receptor-β (PDGFRβ), a marker of pericyte injury 49,67 . BBB breakdown in the hippocampus occurred prior to hippocampal atrophy 49 , which is typically seen early in AD 68,69 , raising the possibility that BBB breakdown might precede neurodegeneration.…”
Section: Neuroimaging Evidence Of Bbb Disruptionmentioning
confidence: 99%
“…Moreover, plasma PDGF-BB levels are increased in AD patients 74 and soluble PDGFRβ (sPDGFRβ) levels, reflecting pericyte injury 75 , are increased in cerebrospinal fluid (CSF) of subjects with mild dementia and transgenic AD and pericyte-deficient murine models 73 , suggesting dysfunction in PDGF-BB/PDGFRβ pathway compared to control subjects and in experimental models.…”
Section: Pericyte-endothelial Signal Transductionmentioning
confidence: 99%
“…Brain capillary pericyte dysfunction results in blood-brain barrier breakdown and contributes to neurological injury (Sagare et al, 2015). PDGFRβ is expressed in the brain by vascular mural cells, brain capillary pericytes and arterial vascular smooth muscle cells, and is a marker for blood-brain barrier disruption (Sagare et al, 2015).…”
Section: Platelet Derived Growth Factor Receptor β (Pdgfrβ)mentioning
confidence: 99%
“…PDGFRβ is expressed in the brain by vascular mural cells, brain capillary pericytes and arterial vascular smooth muscle cells, and is a marker for blood-brain barrier disruption (Sagare et al, 2015). In cultures of human brain pericytes exposed to hypoxia PDGFRβ is a biomarker of pericyte injury (Sagare et al, 2015). Elevated PDGFRβ in biofluids in patients with neurodegenerative disorders likely reflects ongoing pericyte injury and supports its potential to be developed and validated as a biomarker of brain pericyte injury and blood-brain barrier dysfunction (Sagare et al, 2015).…”
Section: Platelet Derived Growth Factor Receptor β (Pdgfrβ)mentioning
confidence: 99%
See 1 more Smart Citation